A propensity score weighted comparison of Vedolizumab, Adalimumab, and Golimumab in patients with ulcerative colitis. Issue 12 (December 2020) - Macaluso, Fabio Salvatore; Ventimiglia, Marco; Fries, Walter; Viola, Anna; Cappello, Maria; Scrivo, Barbara; Magnano, Antonio; Pluchino, Dario; Camilleri, Salvatore; Garufi, Serena; Mitri, Roberto Di; Mocciaro, Filippo; et al.
Abstract: Background: No real-life study on the comparative effectiveness of Vedolizumab (VDZ), Adalimumab (ADA), and Golimumab (GOL) in ulcerative colitis (UC) is currently available. Aims: To compare the effectiveness of the three biologics in consecutive patients with UC. Methods: A three-arms propensity score-adjusted analysis was performed using the Inverse Probability of Treatment Weighting method. Results: 463 treatments (VDZ: n  = 187; ADA: n  = 168; GOL: n  = 108) were included (median follow-up: 47.6 weeks). At 12 weeks ( n  = 463), a steroid-free remission was reported in 24.1% patients in the VDZ group, in 33.3% patients in the ADA group, and in 30.6% patients in the GOL group ( p  =  n .s. for all comparisons). At 52 weeks ( n  = 377), a steroid-free remission was reported in 51.5% patients in the VDZ group, in 31.2% patients in the ADA group, and in 29.4% patients in the GOL group ( p  = 0.002 for VDZ vs. ADA, p  = 0.001 for VDZ vs. GOL, p  =  n .s. for ADA vs. GOL). Cox survival analysis demonstrated that patients treated with VDZ had reduced probability of treatment discontinuation compared to those treated with ADA (HR: 0.42, 95% CI 0.28–0.64, p  < 0.001) and GOL (HR: 0.30, 95% CI 0.19–0.46, p  < 0.001), while patients treated with ADA had reduced risk of treatment discontinuation compared to those treated with GOL (HR: 0.71, 95% CI 0.50–1.00, p  = 0.048). Conclusions: VDZ was superior to ADA and GOL at 52 weeks and as treatment persistence, while ADA showed a superior treatment persistence compared to GOL.